Breaking through bureaucracy : how corporate entrepreneurs create, protect and commercialize their breakthrough business ideas - Lynn, Gary S.; Lynn, Norman M. (Chicago, Ill. : Probus Pub. Co., 1994)
Offers employees advice on how to create and implement products and ideas within the company.
Reprint. Originally published: Innopreneurship. 1992.
Includes bibliographical references (p. 221-245) and index.
oif 13/03/15
Loan
Keywords: New products; Technological innovations; Creative ability in business; Corporate culture; Industrial management; Entrepreneurship; Creative thinking